The effect of computer-assisted audit techniques and professional ethics on audit performance - Mariana; Manurung, Elizabeth T. (Proceeding International Conference on Accounting and Finance, 2023)
In today’s competitive business environment, it’s mandatory for companies to provide financial information that has been audited by a public accounting firm. The audit process is carried out by auditors in accordance with accounting professional ethics and with the use of CAATs. Professional ethics and CAATs will help the auditors perform better during the process, resulting in high-quality and unbiased audit results for the company’s financial statements. This research was conducted using the hypothetico-deductive method, and samples were taken from the public accounting firms in Bandung and Jakarta, which were selected by the purposive sampling method. The data was processed using the SPSS Statistics version 26 application, and the successive interval method was used to analyze it. The validity and reliability of the data were also verified, and the hypothesis was tested with partial tests and simultaneous tests after being assessed using multiple regression and coefficient of determination. According to the findings of this study, CAATs have no effect on auditor performance; however, professional ethics have an effect on auditor performance. Furthermore, when examined simultaneously, the usage of CAATs and professional ethics had a significant effect on auditor performance. Despite the fact that the results of this study indicate no influence, the recommendation is that auditors be encouraged to pay attention to CAATs. Then, public accounting firms are urged to continue providing auditors with technical capabilities. Furthermore, future researchers should create a research unit with a balanced respondent population from each location in order to describe more precise results.